S100A9 protein activates microglia and stimulates phagocytosis, resulting in synaptic and neuronal loss - Katryna Pampuscenko; Silvija Jankeviciute; Ramune Morkuniene; Darius Sulskis; Vytautas Smirnovas; Guy C. Brown; Vilmante Borutaite (Neurobiology of Disease)
S100 calcium-binding protein A9 (S100A9, also known as calgranulin B) is expressed and secreted by myeloid cells under inflammatory conditions, and S100A9 can amplify inflammation. There is a large increase in S100A9 expression in the brains of patients with neurodegenerative diseases, such as Alzheimer's disease, and S100A9 has been suggested to contribute to neurodegeneration, but the mechanisms are unclear. Here we investigated the effects of extracellular recombinant S100A9 protein on microglia, neurons and synapses in primary rat brain neuronal-glial cell cultures. Incubation of cell cultures with 250–500 nM S100A9 caused neuronal loss without signs of apoptosis or necrosis, but accompanied by exposure of the “eat-me” signal - phosphatidylserine on neurons. S100A9 caused activation of microglial inflammation as evidenced by an increase in the microglial number, morphological changes, release of pro-inflammatory cytokines, and increased phagocytic activity. At lower concentrations, 10–100 nM S100A9 induced synaptic loss in the cultures. Depletion of microglia from the cultures prevented S100A9-induced neuronal and synaptic loss, indicating that neuronal and synaptic loss was mediated by microglia. These results suggest that extracellular S100A9 may contribute to neurodegeneration by activating microglial inflammation and phagocytosis, resulting in loss of synapses and neurons. This further suggests the possibility that neurodegeneration may be reduced by targeting S100A9 or microglia.